Porphyromonas gingivalis peptidylarginine deiminase substrate specificity - Syatirah Najmi Abdullah; Farmer, Elizabeth-Anne; Spargo, Llewellyn; Logan, Richard; Gully, Neville (Elsevier Sci Ltd, 2024)
Indexed by WOS/ Scopus